2012
DOI: 10.4314/wsa.v38i2.3
|View full text |Cite
|
Sign up to set email alerts
|

The response of microalgal biomass and community composition to environmental factors in the Sundays Estuary

Abstract: The Sundays Estuary is permanently open to the sea and experiences regular freshwater inflow in the form of agricultural return flows with large supplies of nutrients. The objectives of this study were to measure microalgal biomass and community composition and relate these to freshwater inflow, water quality and other environmental variables. These data can then be used in setting the ecological water requirements of the estuary. Surveys in August 2006, March 2007, February, June and August 2008 showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Marshall and Alden (1990) also concluded that salinity gradients in estuaries were more important than variation in nutrient concentrations in determining the composition of phytoplankton communities. This is however not always the case especially in freshwater dominated estuaries and lakes such as the Nyara Estuary (Walker et al, 2001) and Sundays Estuary (Kotsedi et al, 2012) in South Africa, or the Santragachi lake in, India (Ghosh et al, 2012), where phytoplankton community structure and blooms were mainly due to high nutrient concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Marshall and Alden (1990) also concluded that salinity gradients in estuaries were more important than variation in nutrient concentrations in determining the composition of phytoplankton communities. This is however not always the case especially in freshwater dominated estuaries and lakes such as the Nyara Estuary (Walker et al, 2001) and Sundays Estuary (Kotsedi et al, 2012) in South Africa, or the Santragachi lake in, India (Ghosh et al, 2012), where phytoplankton community structure and blooms were mainly due to high nutrient concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, persistent phytoplankton blooms and nuisance macroalgal growth have been recorded in several estuaries (e.g. Kotsedi et al 2012;Human et al 2016;Lemley et al 2017;. Nationally, deteriorating water quality has been linked to an increase in fish kills and the spread of invasive species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The eutrophication of estuaries caused by human-induced nutrient enrichment is a global environmental concern because of the ecological and economic value of these ecosystems (Cloern et al, 2016). Eutrophication in South Africa appears to be increasing with persistent phytoplankton blooms being reported in a number of other estuaries (Snow et al, 2000;Kotsedi et al, 2012;Kaselowski and Adams, 2013;Lemley et al, 2018). By applying the pelagic component of a eutrophic condition index, proposed by Lemley et al (2015), the eutrophic condition of the Swartkops Estuary could be assessed (Table 1).…”
Section: Discussionmentioning
confidence: 99%